Evolution of codon usage in bacteria - Henry, Ian (2007)
Initially, this thesis investigates patterns of intragenomic codon usage within the genome of the Delta Proteobacterium Bdellovibrio bacteriovorus. Correspondence analyses revealed the primary factor influencing codon usage within this genome to be related to translational selection. The relationship between the degree of codon usage adaptation (as given by the ‘frequency of optimal codons’ statistic) and putative gene expression level was used to look for genes with unusually high or low expression levels in B. bacteriovorus, in comparison to Escherichia coli, in order to gain further insight into the unusual lifestyle of this Delta Proteobacterium.